Rola tożsamości w aliansach strategicznych - Aniszewska, Grażyna (The role of corporate identity in strategic alliances, 2006)
This paper concerns a phenomena of corporate identity and its influence on integration process and effectiveness of organization. The speed and complexity of integration in alliances create conditions to quick learning and changing behaviors. This process can be supported or impeded by the mechanism of corporate identity. There are three phases of integration in the strategic alliances. High degree of alliance cooperation is related to the growing importance of corporate identity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 20-27